Three Separate Cases of Polypoid Endometriosis Coincided with Abscess, Angioleiomyoma or Stromal Sarcoma - Wu Z; Xu Q; Sun Y; Ruan F (International Journal of Women's Health)
Zaigui Wu,1,2 Qiong Xu,3 Yao Sun,4 Fei Ruan1,2 1Department of General Gynecology, Women’s Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 2Zhejiang Provincial Clinical Research Center for Obstetrics and Gynecology, Hangzhou, People’s Republic of China; 3Department of Radiology, Women’s Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 4Department of Pathology, Women’s Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of ChinaCorrespondence: Fei Ruan, Department of General gynecology, Women’s Hospital, School of Medicine, Zhejiang University, Xueshi Road 1, Hangzhou, Zhejiang, People’s Republic of China, Tel +86 159 571 930 58, Email 5202014@zju.edu.cnBackground: Polypoid endometriosis is rare and differs from classic endometriosis. It has been primarily documented in case reports and often misdiagnosed as malignancy. The aim of this study is to report three separate cases of polypoid endometriosis coincided with multiple abscess, angioleiomyoma or stromal sarcoma, respectively.Case Presentation: The first case was 36 years old and presented with six months of dysmenorrhea and menstrual fever. Two cervical masses, one located in vaginal and one in pelvic, were detected by ultrasound. After a total hysterectomy, she was diagnosed with cervical polypoid endometriosis with multiple abscess. The second case aged 36-years too and had menstrual bleeding prolonged to 10– 15 days for four months. Ultrasound showed a 6cm mass like leiomyomas but with rich vascularity, while MRI tested signal intensity similar to that of endometrium. A diagnosis of polypoid endometriosis coincided with angioleiomyoma was made after surgery. The third patient was 40 and experienced lower abdominal pain for eight months. The ultrasound and MRI tested multiple solid-cystic masses in the left ovary and pelvic. The subsequent pathology revealed extensive stromal nodules in various areas such as bilateral ovaries, posterior uterine wall, intestinal tract and left ureter, indicating the diagnosis of low malignant potential stromal sarcoma.Conclusion: Polypoid endometriosis coincided with multiple abscess, angioleiomyoma or stromal sarcoma are rather rare and require aggressive surgical treatment.Keywords: polypoid endometriosis, abscess, angioleiomyoma, stromal nodules, case series